Force-Guided Robot In Mobile Phone Assembly [TK6570.M6 K82 2004 ff rbrb Kejuruteraan] [Microfiche 7706]. - Kong, Suh Chin (2004)
Assembly of mobile phone is currently carried out manually by human operation.